1998
DOI: 10.1037/1099-9809.4.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and negative symptoms in patients with schizophrenia.

Abstract: The purpose of this study was to assess ethnic differences in the negative symptom profile of 25 Anglo American and 26 Mexican American subjects with schizophrenia. Subjects were rated at the end of a 1-2-week medication washout period (time 1) and at discharge (time 2) with the Negative Symptoms Assessment (NSA), Brief Psychiatric Research Scale, (BPRS), the [Diagnostic and Statistical Manual of Mental Disorders (4th edition)] DSM-I\ 7 negative factor sarre and LAF.CA acculturation scale. Total NSA scores wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…More frequent help seeking for depression may be reinforced by somatization, which increases the likelihood of using physicians as a first source of treatment, with a subsequent referral to mental health care for depression. [43][44][45]…”
Section: Self-selectionmentioning
confidence: 99%
“…More frequent help seeking for depression may be reinforced by somatization, which increases the likelihood of using physicians as a first source of treatment, with a subsequent referral to mental health care for depression. [43][44][45]…”
Section: Self-selectionmentioning
confidence: 99%
“…This in particular concerns persons with a visible minority status who could be more prone to perceived discrimination; an experience that is associated with higher levels of positive and depressive symptoms [17] in particular more delusions [18]. Studies from the UK, USA, Germany and the Netherlands have found more severe affective [19,20], positive [21][22][23] , and negative symptoms [24][25][26] in patients from a large variety of immigrant-and ethnic minorities. Others report more depressive symptoms in patients from the majority populations [22,[27][28][29] while still others find similar symptom profiles between minority and majority groups [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of research has begun to investigate the association between ethnicity and symptom severity of schizophrenia. Dassori, Miller, Velligan, Saldana, Diamond and Mahurin 1 conducted a study to examine ethnic differences in symptomatology using a sample of Mexican‐American and Anglo‐American patients diagnosed with schizophrenia to assess if negative symptoms manifested differently between the ethnic groups; compared with Anglo‐Americans, Mexican‐Americans presented with more severe negative symptoms than Anglo‐Americans. With a larger sample of 184 community‐based individuals diagnosed with schizophrenia, Brekke and Barrio 2 investigated the symptom differences between African‐Americans, Latinos and Whites; they found that the non‐minority group was more symptomatic than minority groups, and the differences remained significant after controlling for socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the use of various measurement instruments with different psychometric properties might also explain the mixed findings. Third, some studies did not control for factors that have been found to be associated with severity of psychotic symptoms 1,2 such as gender, 6 duration of untreated illness, 7 premorbid functioning 8,9 and age of onset of illness 10 . Moreover, large majority of the study samples did not consist exclusively of treatment‐naive first‐episode individuals, so symptom severity might have been confounded by several clinical variables such as medication dosage and use, duration of illness, and/or number of relapses experienced.…”
Section: Introductionmentioning
confidence: 99%